An experiment to save the world - Murray, Colin; BBC Scotland Production (United States : BBC Active, 2006)
The power of nuclear fusion is the force at the heart of the sun. If it can be harnessed, it could herald a world of endless, cheap energy. For 40 years scientists have toilet to find this Holy Grail. American scientist Rusi Taleyarkahn has controversially claimed to have found a new way to make nuclear fusion in the lab-using sound waves. In an exclusive experiment, this programme attempts to prove his doubters wrong. What would the world be like if fusion is eventually achieved
Title from title screen
Editor, Matthew Barrett ; photography, Andy Ford, Danny Dimitroff ; sound, Mike Belacicco, Adrian Jaques
Narrator, Dilly Barlow
Keywords: Nuclear fusion -- Experiments